Teaching methods and types of games in teaching Turkish as a foreign language (Journal of Oriental Studies, 2017)
This article investigates methods of teaching new words of Turkish languageby learning as association by drawing shapes and pictures on boardare shown which is motivated of training foreign language. And also it isconsidered importance and role training games in studying of the Turkishlanguage of foreign students.